Detection of metabolomic profile of saliva in healthy Malaysian adults / Han Hing Lee … [et al.] - Han Hing Lee (Faculty of Dentistry, 2015)
Background: Saliva is a readily accessible biofluid that is important for the overall quality of life, functionally essential in the chewing, swallowing, tasting, regulation mouth flora and prevention of caries. The aim of this study is to assess the global metabolomic profile of saliva in healthy Malaysian adults. Methods: As a first step to determining and understanding the metabolomic profile of saliva in healthy Malaysian adults, we have collected saliva samples of 50 adults and measured the salivary metabolite to establish a profiling metabolite data, Human Metabolome Database (HMDB). Metabolites concentrations of saliva in healthy subjects were measured by using 1H NMR spectroscopy. Results: The results showed there was no significant inter-individual variations of the key metabolites observed among the healthy Malaysian adults and there was no significant variation of the metabolites between female and male subjects. Conclusion: The metabolomic profile of saliva in healthy Malaysian adults could be used to establish the metabolomic database and used as a comparison for future study of the saliva of specific diseases.